2016
DOI: 10.21037/tgh.2016.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metastasis from signet ring cell esophageal adenocarcinoma

Abstract: Symptomatic skeletal muscle metastasis from esophageal adenocarcinoma is rare. Here we report the case of a 49-year-old man who presented with right thigh pain, and was found to have symptomatic psoas muscle metastasis as the presentation of esophageal adenocarcinoma. The primary tumor was notable for signet ring cells (SRC), a poor prognostic indicator as well as a predictor of biologic aggressiveness. The patient passed away within 1 month of diagnosis due to disease progression, supporting the aggressivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…9 Although the mechanism of SRCC metastasis to skeletal and cardiac muscle is unclear, it is thought to occur through hematogenous spread of tumor, particularly because these tissues are well-vascularized. 8 Of note, the paravertebral muscles are the most frequently involved site of muscle metastases from a gastric primary. 10 Although gastrointestinal endoscopy is the gold standard for SRCC as it is for other types of gastric cancers, SRCC is particularly difficult to diagnose because it has high false-negative rates of endoscopic biopsy results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Although the mechanism of SRCC metastasis to skeletal and cardiac muscle is unclear, it is thought to occur through hematogenous spread of tumor, particularly because these tissues are well-vascularized. 8 Of note, the paravertebral muscles are the most frequently involved site of muscle metastases from a gastric primary. 10 Although gastrointestinal endoscopy is the gold standard for SRCC as it is for other types of gastric cancers, SRCC is particularly difficult to diagnose because it has high false-negative rates of endoscopic biopsy results.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of patients with skeletal muscle metastasis from diverse primaries reported a mean survival of 9 months from the diagnosis of muscle metastasis. 8 There are several reports and reviews highlighting the development of SRCC in the gastrointestinal system, but there are very few reported cases of this malignancy presenting as metastasis to the peripheral musculature. 8 The incidence of skeletal metastasis is unknown, but approximately 0.16%–0.03% has been reported in clinical practice, and 0.8% in an autopsy study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor metastasis is the main cause of mortality associated with esophageal squamous cell carcinoma ( 6 ). Due to the lack of serous layer in the esophageal wall, direct infiltration and metastasis can occur in the early stage of esophageal cancer ( 7 ). It has been reported that 56% of patients have suffered from blood vessel metastasis and 32% of patients have suffered from lymph metastasis during tumor invasion of the submucosal tissue ( 8 ).…”
Section: Introductionmentioning
confidence: 99%